C-Reactive Protein: An Indicator of Complications in Meningococcal Meningitis - Jamil, Shahid; Khan, Pervez; Rehman, Masood ur; Rizvi, Farhat (Journal of Postgraduate Medical Institute, 2011)
Twenty five culture positive patients with Meningococcal disease were selected out of a total of 221. C-Reactive proteins (C.R.P) at the time of admission and during follow-up were done. This cheap and easy test was found to be a reliable predictor of complications occurring during the course of illness. This test is of course of no help in predicting complications occurring in the initial phase of the illness like sensorineural deafness. The complications noted were hemipelgia, seizures, deafness, prolonged coma, tinnitus, facial palsy and defective vision.